STUDY OF THE EFFECT OF DIFFERENT CONCENTRATIONS OF HUMATEDORGANO-MINERAL FERTILIZER ON THE GROWTH, DEVELOPMENT OF TOMATO AND BELL PEPPER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The scientific article discusses the results of a laboratory study of the effect of various concentrations of humatedorgano-mineral fertilizer obtained from oxidized brown coals of Kyrgyzstan on the growth and development of a plant: tomato and bell pepper.
Keywords: Coal, humic substances, organic raw materials, plants, growth development.